When Is a Liability Not a Liability? Textual Analysis, Dictionaries, and 10‐Ks - LOUGHRAN, TIM; MCDONALD, BILL (Journal of Finance, 2011)
ABSTRACT Previous research uses negative word counts to measure the tone of a text. We show that word lists developed for other disciplines misclassify common words in financial text. In a large sample of 10‐Ks during 1994 to 2008, almost three‐fourths of the words identified as negative by the widely used Harvard Dictionary are words typically not considered negative in financial contexts. We develop an alternative negative word list, along with five other word lists, that better reflect tone in financial text. We link the word lists to 10‐K filing returns, trading volume, return volatility, fraud, material weakness, and unexpected earnings.